2016
DOI: 10.1002/iub.1465
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of pomegranate methanolic extract in antagonizing the endogenous SERM, 27‐hydroxycholesterol

Abstract: The direct relationship between obesity and breast cancer has been elucidated recently with the identification of a cholesterol derivative 27-hydroxycholesterol (27HC), an endogenous SERM that can act through estrogen receptor (ER)-mediated mechanisms. Our recent research shed light on the possible SERM-like property of methanol extract of pericarp of pomegranate (PME) by using human breast (MCF-7, MDA-MB-231), endometrial (HEC-1A), cervical (SiHa, HeLa), ovarian (SKOV3) cancer cell lines, normal breast fibrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…In mouse models evaluating MCF-7 ×enografts in ovariectomized animals, 27-HC administration results in increased circulating 27-HC concentrations and increased tumor volume (4,7), whereas growth is halted following 27-HC withdrawal (4). Modulation of 27-HC has been proposed as a potential therapeutic method for breast cancer (4,7), with studies investigating 27-HC antagonism ongoing in breast cancer cell lines (8). However, to the best of our knowledge, the effect of 27-HC has not been studied in glioblastoma.…”
Section: Introductionmentioning
confidence: 99%
“…In mouse models evaluating MCF-7 ×enografts in ovariectomized animals, 27-HC administration results in increased circulating 27-HC concentrations and increased tumor volume (4,7), whereas growth is halted following 27-HC withdrawal (4). Modulation of 27-HC has been proposed as a potential therapeutic method for breast cancer (4,7), with studies investigating 27-HC antagonism ongoing in breast cancer cell lines (8). However, to the best of our knowledge, the effect of 27-HC has not been studied in glioblastoma.…”
Section: Introductionmentioning
confidence: 99%
“…Methanol extract of pericarp of pomegranate (PME) binds to ER and causes downregulation of the estrogen response element-mediated transcription in breast cancer lines. Moreover, PME can antagonize 27-hydroxycholesterol (an endogenous SERM associated with postmenopausal breast cancer) activity (Vini et al, 2016). Pomegranate extract (PE) can halt the abnormal multiplication of MCF-7 breast cancer cells as well as induce apoptosis in MCF-7 cell line.…”
Section: Breast Cancermentioning
confidence: 99%
“…Furthermore, PME was found to be associated with the ER and caused abrupt expression of estrogen response elements (ERE) [81]. It has also been reported that PME suppressed ER-positive breast tumor growth and proliferation via SERMs [82].…”
Section: Pomegranate and Breast Cancermentioning
confidence: 98%
“…This aromatase enzyme has been found to play a crucial role in tumorigenesis and takes part in the conversion of androgen to estrogen [78,79]. 27hydroxycholesterol (27HC), an endogenous selective estrogen receptor (ER) modulator (SERM), which is a primary metabolite of cholesterol and an ER and liver X receptor (LXR) ligand, has been found to be responsible for ER-dependent growth in breast cancer [80,81]. The methanolic extract of the pomegranate pericarp (PME) down-regulated the activity of 27HC and led to reduced cell growth and proliferation of breast cancer cells.…”
Section: Pomegranate and Breast Cancermentioning
confidence: 99%